An economic impact analysis of a proposed Local Enhanced Management Area for Groundwater Management District #4 - Liebsch, Kellen (Kansas State University, 2018)
While Kansas, and specifically western Kansas, are known by many to be the backbone of agriculture in our nation, much of that productivity has been built on the heels of the invention and efficiency of irrigation technology. Unfortunately, recharge and replenishment of the High Plains - Ogallala Aquifer has not kept pace with the demands of agricultural production, and current indications state that without the implementation of conservation or management practices that the aquifer in Kansas could be depleted by 2060 (Steward, et al. 2013). The producers of Kansas are committed to long-term solutions to preserve their way of life, espouse their commitment to natural resources and the environment, and ensure the viability of their operations for years to come. This study analyzed the economic impact of a proposed Local Enhanced Management Area (LEMA) for Groundwater Management District (GMD) #4. While there currently is a LEMA in a portion of GMD #4 known as the Sheridan 6 LEMA, the board of GMD #4 has initiated the process to institute a district-wide LEMA that would affect a large portion of the 10-county area of the groundwater management district (Cheyenne, Rawlins, Decatur, Sherman, Thomas, Sheridan, Graham, Wallace, Logan, and Gove Counties). To complete the analysis for the proposed policy change, multiple scenarios were derived using the IMPLAN software. The first model serves as the baseline scenario and provides status quo information on the current irrigated cropping economics of GMD #4. The second scenario assumes that a district-wide LEMA would require a 25% reduction in groundwater use, compared to current irrigation practices. To achieve this reduction in groundwater use, irrigated acreage was reduced by 25% and transitioned to dryland production. For the third and final scenario, an optimal irrigated crop-mix ratio is determined based on the current shift in production as reported by the producers in the Sheridan 6 LEMA. While this scenario does not reduce irrigated acres, it shows the economic gains that can be captured by using less water-intensive crops as part of the crop-mix ratio. The reduction in irrigation is also imbedded in that the acreage in which production is shifted away from is more water intensive towards acreage that is less water-intensive. Due to a reduction in groundwater use for irrigation, the study determined that there is a negative economic impact in relation to employment and total output in the GMD #4 area. There are 173 less individuals employed from the 25% reduction in groundwater use. Additionally, direct output is reduced by $44.6 million and total output is reduced by $60.0 million. This equates to a $194.49 reduction per acre on a per-acre basis. The study further showed that the economic impact could be lessened by the use of a crop-mix shift as evidenced in the current Sheridan 6 LEMA. The assessment of a crop-mix shift decreased the loss of direct output by $12.0 million to $265.0 million and total output by $16.5 million to $357.1 million. On a per-acre basis, this is a reduction of $140.97, or mitigation of $53.52 in loss per acre due to the use of an optimal crop-mix shift. While agricultural production is highly dependent on many factors, it can be universally agreed that the landscape of agriculture would be different if water was not an available resource. It is the hope that this research will provide a starting point for the producers of GMD #4 to have a conversation about the economic costs associated with the implementation of a LEMA, as well as discuss other options and opportunities to make educated, well-informed decisions that are impactful both now and for generations to come.
Keywords: Ogallala; IMPLAN; Conservation; Groundwater Management District 4; LEMA